Kreativitas Guru dalam Menumbuhkan Minat Belajar Siswa Pada Pembelajaran Geografi Di SMA Negeri 1 Lore Utara Kabupaten Poso - Sefriana, Simpil; Jamaluddin (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2023)
This study aims to determine the teacher's creativity in cultivating student interest in learning and knowing the factors that influence students' interest in learning Geography. The method used is descriptive qualitative, with 1 geography teacher as the subject of the research. Data collection techniques with observation, interviews and documentation. data analysis used is interactive model data analysis. The research results show that; 1) Forms of teacher creativity, various kinds of creativity are carried out when teaching, by providing entertainment such as humor and quizzes, using teaching aids, learning outside the classroom or to places that are appropriate to the ongoing material, just around the school environment or locations outside the school that are affordable. 2) Student interest in geography subjects with a fairly good student interest in learning. So, the material taught by the teacher is easy to understand. Students become easy and can remember it. Students' sense of interest can generate feelings and attitudes, both feelings of pleasure, feelings of interest, attitudes that are full of attention, and carry out a positive attitude. 3) The causes of factors that affect students' interest in learning both internal factors, namely; students are easily influenced from the health aspect and student concentration in learning that is less supportive of the individual in learning readiness at school. External factors are family factors, and school factors as well as social factors among friends at school in the community.